Outcomes of reverse shoulder arthroplasty following failed superior capsular reconstruction - Cusano, Antonio; Kanski, Gregory; Uyeki, Colin; Adams, Kyle; Cote, Mark P.; Muench, Lukas N.; Connors, John Patrick; Garvin, Patrick; Messina, James C.; Berthold, Daniel P.; Kissenberth, Michael J.; Mazzocca, Augustus D. (Journal of shoulder and elbow surgery, 2022)
Superior capsular reconstruction (SCR) can be used for massive irreparable rotator cuff tears in the absence of significant degenerative changes; however, those who fail an SCR may require reverse shoulder arthroplasty (RSA). The effect of a previously performed SCR on outcomes following RSA remains unknown. Subjects who underwent RSA from May 2015 to January 2021 at 2 separate institutions were retrospectively identified through prospectively collected databases. Patients who underwent RSA after failed SCR were matched to those who underwent RSA after failed rotator cuff repair (RCR) based on the number of previous ipsilateral shoulder procedures (n = 1, 2, ≥3) and secondarily by age within 5 years. American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form (ASES) score, Single Assessment Numeric Evaluation (SANE), visual analog scale (VAS) for pain, and Western Ontario Osteoarthritis of the Shoulder index (WOOS) scores were compared between groups. The minimal clinically important difference (MCID), substantial clinical benefit (SCB), and patient acceptable symptomatic state (PASS) thresholds were calculated to determine clinically relevant differences between groups. Forty-five patients were included (32 RSA following RCR, 13 following SCR). There were more smokers (P = .001) and worker's compensation cases (P = .034) in the SCR group. The RCR cohort was older (P = .007) and had a greater incidence of mental health (P > .999) and somatic disorders (P = .698), although these did not reach statistical significance. The mean follow-up for the RCR and SCR groups were 24.2 ± 23.3 and 20.4 ± 14.9 months following RSA, respectively (P = .913). The time from index RCR or SCR to RSA were 94.4 ± 22.2 and 89.2 ± 5.3 months, respectively (P = .003). Pre- and postoperative range of motion were similar between groups, as was the overall change in forward flexion (P = .879), abduction (P = .971), and external rotation (P = .968) following RSA. The RCR group had lower postoperative VAS pain (P = .009), higher SANE (P = .015), higher ASES (P = .008), and higher WOOS (P = .018) scores. The percentage achieving the MCID (P = .676) and SCB (P > .999) were similar; however, 56.7% of the RCR group met the SANE PASS threshold compared with 0.0% in the SCR group (P = .005). There were no differences in postoperative complications (P = .698) or revision rates (P = .308) following RSA between cohorts. When matched for number of previous procedures to the ipsilateral extremity and age, patients who underwent RSA following failed SCR had worse clinical outcome scores than their RSA following failed RCR counterparts. No patient in the SCR group met the SANE PASS threshold, whereas more than half of the RCR group did.